Employment Legal Protection in Facing Artificial Intelligence Disruption: Efforts to Overcome the Replacement of Human Workers - Cece Suryana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study aims to analyze employment legal protection in the face of disruption from artificial intelligence (AI) technology that threatens the existence of human labor. The development of AI technology has created new challenges for the world of employment, where many jobs have the potential to be replaced by machines and automated systems. This study uses a normative legal method with a statutory approach to examine existing employment regulations and their relevance in protecting workers' rights in the digital era. The data used consists of legal literature, laws and regulations related to the application of AI in the world of work. The results of the study show that Law Number 13 of 2023 concerning Manpower emerged as a response to the unfavorable situation for workers, with the aim of protecting labor rights and implementing international instruments and human rights declarations. Technological advances, especially automation and artificial intelligence (AI), bring benefits such as efficiency and new opportunities, but also pose challenges such as job loss. To address this, the government needs to strengthen employment legal protection, design policies to support affected workers, and provide skills training and incentives for companies. The Circular of the Ministry of Communication and Information on the ethics of using AI emphasizes inclusivity, humanity, accessibility, and sustainable development, as well as the protection of workers' rights such as the right to work and fair treatment. However, current national regulations do not specifically regulate the use of AI by companies, so new legal arrangements are needed to protect workers' rights and manage the transition due to Termination of Employment.